Simultaneous Determination of Water and Fat-Soluble Vitamins in Pekmez Samples by High Performance Liquid Chromatography Coupled with Diode Array Detection - Zehra Küçükbay, F.; Karaca, Idil (Asian Journal of Chemistry, 2010)
In the present work, a RP-HPLC procedure has been applied for the determination of watersoluble vitamins (riboflavin, nicotinamide, pantothenic acid, pyridoxine hydrochloride, pyridoxal, folic acid, ascorbic acid) and fat-soluble vitamins (trans-retinol, α-tocopherol) in pekmez samples, a tradional Turkish concentrate fruit food. The sample treatment proposed consists of a solid-phase extraction with Sep-Pak C18 cartridges that allow the seperation of fat-soluble vitamins, which were retained on the sorbent, from water-soluble vitamins. After isolation of the two fractions, the water-soluble vitamins were analyzed by HPLC on an ACE 5 C18 (250 × 4.6 mm, 5 μm) analytical column using 0.1 mol L-1 KH2PO4 (pH 7.0)-CH3OH as mobile phase. The chromatographic analysis of the fat-soluble vitamins was carried out after their sequential elution with CH3OH-CCl4 from C18 sorbent, on the above column. Afterwards, the fat-soluble vitamins were analyzed on an ACE 5 C18 analytical with isocratic mobile phase consisting of CH3OH-CH3CN at a flow-rate of 2 mL min-1. Identification of compounds was achieved by comparing their retention times and UV spectra with those of standards stored in a data bank. The accuracy of the method was tested obtaining an average recovery ranging between 91 and 110 %.